Factors associated with survival after pediatric in-hospital cardiac arrest: A national database analysis 2015–2022 - Rattapon Uppala; Phanthila Sitthikarnkha; Sirapoom Niamsanit; Kaewjai Thepsuthammarat; Leelawadee Techasatian; Suchaorn Saengnipanthkul; Pope Kosararaksa; Sysavanh Nanthavongsa; Akihiro Nishi (PLoS ONE, 2026)
Background Pediatric in-hospital cardiac arrest (IHCA) is frequently fatal, and evidence from middle-income settings needed to guide quality improvement is sparse. We used nationwide Thai data to quantify incidence and mortality trends, describe long-term outcomes, and identify associated factors for post-discharge death after pediatric IHCA. Methods We performed a retrospective cohort study using the Thai National Health Security Office database encompassing all hospitalizations under the universal health-coverage scheme from 1 January 2015–31 December 2022. Children <18 years with IHCA were identified by ICD-10-TM codes I46.0/I46.1/I46.9 plus at least one resuscitation procedure code (ICD-9-CM 99.60/99.62/99.63). All-cause mortality through 31 December 2023 was obtained via linkage to the national civil registry. Results Among 13.2 million pediatric admissions, 20,590 IHCAs were recorded (incidence 1.57/1,000). Incidence declined from 1.8/1,000 in 2015–2016 to 1.2/1,000 in 2022. In-hospital mortality was 62.7% (12,905/20,590). Of 7,253 survivors with follow-up (median 67 months), 2,149 (29.6%) died post-discharge. Multivariable analysis identified metabolic acidosis (adjusted hazard ratio [aHR] 1.50; 95% confidence interval [CI] 1.32–1.71) and hypoglycemia (aHR 1.54; 95% CI 1.25–1.89) as significant associated diagnoses with long-term mortality. Furthermore, diagnoses consistent with severe organ dysfunction, including disseminated intravascular coagulation (aHR 1.51; 95% CI 1.24–1.85), acute liver failure (aHR 1.42; 95% CI 1.10–1.84), and anoxic brain injury (aHR 1.23; 95% CI 1.05–1.44), were also significantly correlated with increased mortality; however, the timing of these diagnoses relative to the cardiac arrest could not be determined. Conclusions Pediatric IHCA in Thailand remains highly fatal despite recent declines in incidence and in-hospital mortality. During a median follow-up of 67 months, nearly one-third of survivors died after discharge, underscoring the substantial long-term mortality burden. Metabolic derangements and organ dysfunction were strongly associated with post-discharge mortality, highlighting the need for targeted strategies to improve both survival and long-term outcomes.